THE CONFUSED WHALE OF THE CHINA SEA: WATER SYMBOLISM IN THE WORKS OF HAMZAH FANSURI - Amir H. Zekrgoo, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Perhaps the most valuable contribution of Hamzah Fansuri to the elevation of intellectual and spiritual traditions of Islam was his tireless efforts to create a harmonious atmosphere between the stern followers of religious law (shari‘ah) and the Sufi ways of self-purification (ṭariqah). The renowned 16th century Malay mystic used simple language to communicate his thoughts to average audience. In order to add clarity to his arguments he often resorted to symbols and metaphors that made his discussions more appealing. This essay begins with a brief introductory remark about the importance of water in religious traditions, followed by a passage on Sufi symbolism in Hamzah’s writings. Among the wide range of symbolic expressions adopted by Hamzah, water-related-metaphors occupy the highest place – both from the viewpoint of their frequent appearance, and in terms of profoundness of their suggestive meanings. Hence, the main body of the paper focuses on water symbolism in Hamzah’s treatises and poems, which is presented under seven headings namely: Waters of Life, Ocean of Unity, Currents of Creation, Waves of Manifestation, Bubbles of Identity, The Confused Whale, and The Brilliant Fish.